THE MINIMALIST ANALYSIS OF THE COST OF USING CEFIXIME AND METRONIDAZOLE ANTIBIOTICS IN BPJS CLASS III PATIENTS WITH CHILD ACUTE DIARRHEA IN THE INPATIENT CARE INSTALLATION OF RSM AHMAD DAHLAN, KEDIRI CITY (JANUARY – JUNE PERIOD) IN 2023 - Sugeng Walujo, Djembor; Ayu Sagita, Fivo (JURNAL PHARMA BHAKTA, 2025)
Diarrhea is a disease caused by bacterial infection characterized by nausea, vomiting, abdominal pain, headache, fever, chills, and discomfort. The choice of antibiotics for the treatment of diarrhea is based on the severity, location of the infection, and type of infecting microorganism. The purpose of the study was to determine the minimum cost of antibiotic use in BPJS class III patients with acute diarrhea in the inpatient installation of RSM Ahmad Dahlan Kediri City from January to June 2023. This study was an observational analytic study with a cross-sectional research design through a retrospective approach. Then the data were analyzed using SPSS, using the Mann Whitney test analysis method. The results showed that metronidazole antibiotics were more cost minimization than cefixime antibiotics with an average of Rp3,663,288 and Rp4,295,103, respectively. Based on the results of the statistical test, the p value was 0.294> 0.05, so it can be interpreted that the amount of direct medical costs between patients using cefixime antibiotic therapy and metronidazole antibiotics did not differ significantly.